Isolation and identification of fungal pathogen causing leaf spot disease in oil palm at nursery stage - Mohd Zahri, Siti Zubaidah (2016)
Oil palm (Elaeis guineensis jacq.) is the most important commodity crop in Malaysia as it contributes 5% of gross national income. Leaf spot disease of oil palm occurs on leaves of all ages particularly on juvenile palms. This disease can cause revenue lost to nursery owners as it affects the growth and quality of the seedlings. Nonetheless, the identity of the causal pathogen is still unknown and often misidentified with other symptoms such leaf blight and anthracnose disease. Therefore the objectives of this study were i. To isolate pathogenic fungi from symptomatic juvenile oil palm leaves ii. To identify the isolated fungus based on morphological and molecular characteristics. Morphological characteristics were studied based on the visible nature and microscopic view of each fungal culture. While for molecular identification, isolated fungal genomic DNA was amplified using ITS1 and ITS4 primer sets and sequenced for identification purpose. The obtained sequences were resulted to BLAST analysis on GenBank sequence database to match the isolates at species level. All the six isolates studied were identified as Lasidiplodia theobromae, Pestalotiopsis microspora, Curvularia eragrostidis, Phoma herbarum and Nigrospora Sphaerica. Lastly, pathogenicity test was conducted on six months old healthy commercial DxP oil palm seedlings. Two potential fungal isolates which may be related to leaf spot disease were selected, P. microspora and C. eragrostidis. As a conclusion, in this study both P. microspora and C. eragrostidis fungi have been identified as the causal pathogen of leaf spot disease on juvenile oil palm seedlings based on the reproducibility of leaf spot symptoms and severity of the foliar symptoms displayed through the pathogenicity test conducted.